Erratum: Genomic variants in mouse model induced by azoxymethane and dextran sodium sulfate improperly mimic human colorectal cancer - Pan, Qingfei (Sci Rep, 2017)
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.